Leptospirosis in Vellore: A Clinical and Serological Study - G. Vimala; A. Mary Josephine Rani; V. Raja Gopal (International Journal of Microbiology)
Leptospirosis is a severe spirochetal zoonosis in the world. It is considered an occupational disease of persons engaged in agriculture, sewage works, forestry, and animal slaughtering. A study was conducted with an objective of assessing the seroprevalence of leptospirosis in and around Vellore district, Tamil Nadu. The study was based on the signs and symptoms of the patients reporting fever in Vellore Municipal Clinic (Urban Malarial Scheme). Blood samples were collected from 129 patients. Animal studies were conducted from 24 rodents captured form the market place of the Vellore municipality. In the ZET (Zonal Entomological Team, Vellore) Laboratory the sera were examined by macroscopic slide agglutination test (MSAT). In the MAST, totally 10 positive leptospiral cases from human beings and 10 positive leptospiral cases from rats (Rattus rattus and Rattus norvegicus) were found out. Then both positive cases of leptospiral vials were labeled, sealed, and sent to the Leptospirosis Research Laboratory, Madhavaram, Chennai, for further serovars examination. Among the various serovars identified autumnalis was more prevalent. Our findings showed that the age groups between 15 and 55 years showed more susceptibility. Particularly the adults were more infected. The majority of seropositive individuals in the cases had only subclinical infection. Rodents were abundant and contributed to enzootic and endemic prevalence of leptospirosis.